Upper Cervical Surgery, Increased Signal Intensity of the Spinal Cord, and Hypertension as Risk Factors for Dyspnea After Multilevel Anterior Cervical Discectomy and Fusion. Issue 7 (1st April 2020) - An, Seong Bae; Lee, Jong Joo; Kim, Tae Woo; Shin, Dong Ah; Yi, Seong; Kim, Keung Nyun; Yoon, Do Heum; Ha, Yoon
Abstract : Study Design: Retrospective study. Objective: To investigate the associated risk factors for acute respiratory distress after multilevel anterior cervical discectomy and fusion (ACDF) with a focus on the subjective symptom, dyspnea. Summary of Background Data: Acute respiratory distress after ACDF is a relatively common adverse event, the cause of which is usually soft tissue swelling or hematoma. It can result in serious morbidity and requires careful, focused treatment. Methods: We reviewed the records of 532 patients (from January 2014 to August 2018) who had undergone multilevel ACDF surgery. Acute respiratory distress was defined as a complaint of dyspnea within 5 postoperative days. We investigated the patients' demographic parameters, comorbidities, and surgical procedure details. We also investigated radiologic parameters, including magnetic resonance imaging (MRI), with special attention to the prevertebral soft tissue thickness at C3 and C6. Statistical analysis was performed using the Student's t test and multiple logistic regression analysis. Results: Out of a total of 484 patients studied after exclusion criteria were applied, 31 patients (6.6%) experienced dyspnea after surgery. We selected 92 patients from the non-dyspnea group and compared them with 31 patients from the dyspnea group. On univariate analysis, upper cervical surgery involving C3, increased cord signal intensity on T2-weighted imaging (T2WI) magnetic resonance imaging (MRI), hypertension, smoking, and prevertebral soft tissue swelling at C3 level on postoperative day 1 were statistically significant factors associated with dyspnea. On logistic regression analysis, upper cervical surgery involving C3, increased cord signal intensity on T2WI MRI, and hypertension were found to be statistically significant variables ( P < 0.05). Conclusion: Patients undergoing upper cervical surgery involving C3, and having increased cord signal intensity on T2WI MRI and hypertension need to be monitored more carefully for acute respiratory distress after multilevel ACDF. Level of Evidence: 4 Abstract : We investigated the risk factors for dyspnea after multilevel anterior cervical discectomy and fusion. Upper cervical surgery involving C3, increased cord signal intensity on T2-weighted imaging magnetic resonance imaging, and hypertension were the associated risk factors. It is necessary to be vigilant and monitor patients carefully when these risk factors are present.